Defy the night eaudiobook - Kemmerer, Brigid (Defy the Night, 2021)
Instant New York Times Bestseller! From New York Times bestselling author Brigid Kemmerer comes an electrifying fantasy romance, perfect for fans of Holly Black and Victoria Aveyard. A desperate prince. A daring outlaw. A dangerous flirtation. In the Wilds of Kandala, apothecary apprentice Tessa Cade has been watching people suffer for too long. A mysterious sickness is ravaging the land and the cure, Moonflower Elixir, is only available for the wealthy. So every night, she defies the royal edicts and sneaks out, stealing Moonflower petals and leaving the elixir for those in need. In the palace of Kandala, Prince Corrick serves as the King's Justice, meting out vicious punishments and striking fear into the hearts of agitators and outlaws. Corrick knows he must play this role convincingly—with a shortage of elixir and threats of rebellion looming ever closer, the King's grip on power is tenuous at best, and Corrick knows his brother is the kingdom's best hope for survival. But when an act of unspeakable cruelty brings the royal and the outlaw face to face, the natural enemies are faced with an impossible choice—and a surprising spark. Will they follow their instincts to destroy each other? Or will they save the kingdom together . . . and let that spark ignite?